EFEKTIFITAS MODEL EKSPOSITORI MELALUI MEDIA VISUAL TERHADAP HASIL BELAJAR SISWA DI SMA - Wulandari, Anggita; Mashudi, Mashudi; Buwono, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims determine the effectiviness of expository teaching model through visual media on economic subjects against haail for students at SMA N 1 Sungai Raya. The research methods used in this study was pre â€“experimnetal design with the design of the study is one group pretest-posttest. The technique used in this study is the technique of measurement and observation. Research subject in this study were student of class XI social sciences 2 totaling 36 people. Analiysis of data obtained by t-test. If the value of t >Â t tabel and significance < 0.005 then Ho rejected. Based onthe calculation of the data obtained t count > t table (9,366>2,030) and significant (0,000 > 0,005). So it can be concluded that the effectiveness of expository teching model through visual media provide high impact on improving student learning outcomes.Keywords : Effectiveness, Learning Model of Expository, Visual Media